Dynamic deformation behavior of a FeCrNi medium entropy alloy. (20th February 2022) - Fu, Ao; Liu, Bin; Li, Zezhou; Wang, Bingfeng; Cao, Yuankui; Liu, Yong
Highlights: The MEA shows high strain-hardening ability and moderate thermal-softening effect. The MEA resists adiabatic shear band formation up to a high shear strain of 14.5. Multiple deformation mechanisms effectively improve shear localization resistance. Abstract: Deformation behavior of a FeCrNi medium entropy alloy (MEA) prepared by powder metallurgy (P/M) method was investigated over a wide range of strain rates. The FeCrNi MEA exhibits high strain-hardening ability, which can be attributed to the multiple deformation mechanisms, including dislocation slip, deformation induced stacking fault and mechanical twinning. The shear localization behavior of the FeCrNi MEA was also analyzed by dynamically loading hat-shaped specimens, and the distinct adiabatic shear band cannot be observed until the shear strain reaches 14.5. The microstructures within and outside the shear band exhibit different characteristics: the grains near the shear band are severely elongated and significantly refined by dislocation slip and twinning; inside the shear band, the initial coarse grains completely disappear, and transform into recrystallized ultrafine equiaxed grains by the classical rotational dynamic recrystallization mechanism. Moreover, microvoids preferentially nucleate in the central areas of the shear band where the temperature is very high and the shear stress is highly concentrated. These microvoids will coalesce into microcracks with the increase of strain, which eventually leads to the fracture of the shear band.